PEMBUATAN KARBON AKTIF DARI CANGKANG KELAPA SAWIT DENGAN MENGGUNAKAN H 2 O SEBAGAI AKTIVATOR UNTUK MENGANALISIS PROKSIMAT, BILANGAN IODINE DAN RENDEMEN - Hafnida Hasni Harahap; Usman Malik; Rahmi Dewi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Activated carbon from shells of oil palm has succesfully been made. It was carbonizedat 400 ̊C, 500 ̊C and 600 ̊C for 20, 40 and 60 minutes. The physical activation wascarried out at the temperature of 900 ̊C for 20, 40 and 60 minutes. This activation wasdone by flowing the water vapor as an activated agent. The objective of this researchwas to characterize palm oil shells that was carried out through proximate test whichwere water content and ash content, the absorbane of activated carbon toward iodinevalue and yield. The best results after carbonization were the samples that werecarbonized at 600 ̊C for 60 minutes, with proximate content : water content of 4,5% andash content of 9.7%. The iodine number at activation of 900 ̊C for 60 minutes was 353mg/ gr and yield of 48%.